Attitudes toward driver's licenses for people with epilepsy: 2012 versus 2014. Issue 2 (7th December 2016) - Okumura, Akihisa; Abe, Shinpei; Nakazawa, Mika; Ikeno, Mitsuru; Igarashi, Ayuko; Takasu, Michihiko; Shimizu, Toshiaki
Abstract: Background: We compared knowledge about and attitudes toward epilepsy and the issuing of driver's licenses to people with epilepsy among non‐medical students before and after media controversies. Methods: The survey was performed in 2012 and 2014 using a structured questionnaire. Participants were non‐medical students who attended a lecture on neurological diseases in children. The proportion of positive answers to each question in 2012 was compared with that in 2014. In addition, questions regarding attitudes toward driver's licenses were compared according to knowledge about car accidents linked to people with epilepsy. Results: More participants were familiar with epilepsy and had a favorable attitude toward epilepsy in 2014 than in 2012. In contrast, the proportion of participants who knew of car accidents linked to people with epilepsy was reduced in 2014 compared with 2012. The proportion of participants who did not think that severe punishment should be given to people with epilepsy if they caused a car accident decreased in 2014 among those without knowledge of car accidents. Conclusions: Familiarity with and attitudes toward epilepsy were improved in 2014, whereas the decrease in proportion of positive answers on punishment among participants unfamiliar with car accidents suggests a latent worsening of public attitudes.